HISTOLOGY OF HEART AND GONAD OF KISSING GOURAMY WITH FEED CONTAINING GLUTATION AND VITAMIN E - Fitriliyani, Indira Fitriliyani (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
The development of Kissing gourami culture is experiencing problems due to the non-optimal development of the gonads and the low quality of the larvae. This study aims to determine the dose of Vitamin E in commercial feed containing glutathione which is optimal for the liver and gonads of Kissing gourami and to determine the histology of the liver and gonads of Kissing gourami. This research was conducted in Puja Kesuma Swimming Pool, Sipai River Irrigation, Martapura District, Banjar Regency, South Kalimantan Province with a maintenance time of ± 5 weeks. The design used in this study was a completely randomized design (CRD) with 4 treatments and 3 replications with the following treatments: A Commercial Feed + containing glutathione 10 mg/kg (CFG); B; CFG + (300 mg/Kg Vitamin E), C; CFG + (500 mg/Kg Vitamin E), D; CFG+ (700 mg/Kg Vitamin E). The results showed that the administration of vitamin E had no significant effect on the parameters of IHS, IGS, egg diameter, and fecundity, whereas in the observation of liver histology, cells with necrosis and gonadal histology at a dose of 700 mg/kg were found to be dominant in stage IV eggs ready for Geminal Vesicle Break Down (GVBD). So, it can be concluded that the combination of Glutathione with vitamin E at a dose of 700 mg/kg of feed is the best.